Effectiveness of Minimally Invasive Hepatectomy in Patients with Early or Intermediate-Stage Hepatocellular Carcinoma: A Multi-Institutional Cohort Study in an Asian Population - Chen HK; Chang KC; Shao SC; Soong RS; Chen YC; Wu CF; Wu TH; Chou TS; Chan SC; Lai ECC (Journal of Hepatocellular Carcinoma)
Hung-Kai Chen,1– 3,* Kai-Cheng Chang,3,4,* Shih-Chieh Shao,4– 6 Ruey-Shyang Soong,7– 9 Yi-Chan Chen,10,11 Chun-Feng Wu,12 Tsung-Han Wu,12 Tien-Shin Chou,13 Siu-Cheung Chan,14 Edward Chia-Cheng Lai4,6 1Department of Pharmaceutical Outcomes and Policy, College of Pharmacy, University of Florida, Gainesville, FL, USA; 2Department of Internal Medicine, Linkou Chang Gung Memorial Hospital, Taoyuan, Taiwan; 3Department of Pharmacy, Linkou Chang Gung Memorial Hospital, Taoyuan, Taiwan; 4School of Pharmacy, Institute of Clinical Pharmacy and Pharmaceutical Sciences, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 5Department of Pharmacy, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan; 6Population Health Data Center, National Cheng Kung University, Tainan, Taiwan; 7Division of General Surgery, Department of Surgery, Shuang Ho Hospital, Taipei Medical University, New Taipei, Taiwan; 8Department of Surgery, Taipei Medical University, Taipei, Taiwan; 9Taipei Cancer Center, Taipei Medical University, Taipei, Taiwan; 10Department of General Surgery, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan; 11College of Medicine, Chang Gung University, Taoyuan, Taiwan; 12Department of Hematology Oncology, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan; 13Department of Gastroenterology, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan; 14Department of Radiology, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan*These authors contributed equally to this workCorrespondence: Ruey-Shyang Soong, Division of General Surgery, Department of Surgery, Shuang Ho Hospital, Taipei Medical University, No. 291, Jhongjheng Rd., Jhonghe, New Taipei, 23561, Taiwan, Tel +886-936170198, Email kodlp62@gmail.comPurpose: Minimally invasive hepatectomy (MIH) has been increasingly applied for patients with hepatocellular carcinoma (HCC). However, the effectiveness of MIH has yet to be well established.Patients and Methods: This retrospective cohort study included patients aged 20 years and older, newly receiving MIH for HCC with Barcelona Clinic Liver Cancer (BCLC) classification stage 0, A or B from 2010 to 2019. Two 1:1 propensity score-matched cohorts of those receiving open hepatectomy (OH) and those receiving radiofrequency ablation (RFA) were selected as comparison groups. As a control analysis, we compared patients receiving OH with those receiving RFA under the hypothesis that the OH group had better survival outcomes than the RFA group.Results: We included a total of 555 matched patients receiving MIH or OH, and 382 matched patients receiving MIH or RFA. Compared to the OH group, MIH group was associated with better overall survival (OS) (Hazard ratios (HR): 0.62; 95% CI: 0.43– 0.88) and similar PFS (HR: 0.92; 0.74– 1.16). Compared to the RFA group, we found the MIH group was associated with better OS (0.46; 0.32– 0.67) and better PFS (0.48; 0.38– 0.61). We found consistent results from a series of subgroup analyses (eg, age groups, BCLC stages and hospital levels) and sensitivity analyses (eg, study period restricted to the most recent 5 years (2015– 2019)). The control analysis (OH group vs RFA group) confirmed the robustness of main analyses.Conclusion: Our study suggested that MIH had better survival outcomes for patients with early or resectable intermediate-stage HCC, compared to RFA or OH.Keywords: hepatocellular carcinoma, minimally invasive hepatectomy, open hepatectomy, radiofrequency ablation, long-term survival